2008
DOI: 10.1086/587433
|View full text |Cite
|
Sign up to set email alerts
|

The Globular Cluster Systems around NGC 3311 and NGC 3309

Abstract: We present extensive new photometry in (g',i') of the large globular cluster (GC) system around NGC 3311, the central cD galaxy in the Hydra cluster. Our GMOS data cover a 5.5' field of view and reach a limiting magnitude i' = 26, about 0.5 magnitude fainter than the turnover point of the GC luminosity function. We find that NGC 3311 has a huge population of ~16, 000 GCs, closely similar to the prototypical high specific frequency Virgo giant M87. The color-magnitude distribution shows that the metal-poor blue… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
95
0
8

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(116 citation statements)
references
References 44 publications
13
95
0
8
Order By: Relevance
“…The pair NGC 3311/NGC 3309 bears some resemblance to the central pair NGC 1399/NGC 1404 in the Fornax cluster with NGC 1404 being also being underabundant in globular clusters (Richtler et al 1992) and clusters actually belonging to NGC 1404 indeed contaminating the cluster system of NGC 1399 (Schuberth et al 2010). However, our sample of NGC 3311 clusters consists exclusively of very bright objects that are genuinely sparse in normal ellipticals, so we expect the contamination by NGC 3309 to be even lower than the 2% quoted by Wehner et al (2008). An additional difference of NGC 1399/NGC 1404 is visible in the X-ray isophotes.…”
Section: The Role Of Ngc 3309 and Remarks On The Validity Of Equilibriummentioning
confidence: 68%
“…The pair NGC 3311/NGC 3309 bears some resemblance to the central pair NGC 1399/NGC 1404 in the Fornax cluster with NGC 1404 being also being underabundant in globular clusters (Richtler et al 1992) and clusters actually belonging to NGC 1404 indeed contaminating the cluster system of NGC 1399 (Schuberth et al 2010). However, our sample of NGC 3311 clusters consists exclusively of very bright objects that are genuinely sparse in normal ellipticals, so we expect the contamination by NGC 3309 to be even lower than the 2% quoted by Wehner et al (2008). An additional difference of NGC 1399/NGC 1404 is visible in the X-ray isophotes.…”
Section: The Role Of Ngc 3309 and Remarks On The Validity Of Equilibriummentioning
confidence: 68%
“…Harris et al 2006Harris et al , 2009aStrader et al 2006;Mieske et al 2006Mieske et al , 2010Spitler et al 2006;Humphrey 2009;Cockcroft et al 2009;Forbes et al 2010;Blom et al 2012;Usher et al 2013). This phenomenon has been nicknamed the blue tilt, and has also been detected through ground-based imaging (Forte et al 2007;Wehner et al 2008;Park 2012). The first strong hint of the existence of such a colour-magnitude relation of GCs was reported in Dirsch et al (2003), who found that the colour distribution of the brightest GCs in NGC 1399 becomes broad and unimodal.…”
Section: Colour Magnitude Relation Of Extragalactic Globular Clustersmentioning
confidence: 88%
“…Value of the blue tilt slope γ = d(U − I)/dI and of the mass-metallicity relation exponent α obtained for Centaurus and Hydra with our data for the range I < 24.0 mag, compared to results of previous studies on these clusters and other environments. (Wehner et al 2008) 0.60 ± 0.20 BCGs (Harris et al 2009a) 0 . 4 8 ± 0.12 −0.11 ± 0.06 M104 0 .…”
Section: Discussionmentioning
confidence: 99%
“…which gives a good analytical description of the completeness, and which has been used for many GC studies (e.g., McLaughlin et al 1994;Fleming et al 1995;Wehner et al 2008;Alamo-Martínez et al 2012). The free parameters α and m 50 indicate the speed at which the detection rate falls at the faint level and the 50% completeness, respectively.…”
Section: Photometry Completenessmentioning
confidence: 99%
“…2 as large black points, while resolved sources are depicted will small black dots. Globular cluster candidates were further limited to the color range 0.4 < (g − i) 0 < 1.4, following previous GCS studies with the same filters Wehner et al 2008;Faifer et al 2011), but with a slightly bluer limit to allow studying possible younger clusters (as in NGC 2685 Sikkema et al 2006). The bright limit was fixed at M i = −11.5 following Faifer et al (2011), and the faint limit was given by the 80% completeness limit in both g and i.…”
Section: Gc Color Distributionmentioning
confidence: 99%